Textual organization and discussion applied to the “jornalistic column” genre - Mendonça, Igor Frontelmo; Silva, João Antônio Lopes da (Revista de Iniciação à Docência, 2024)
This project reports the experience undergone in the making of the workshop “Textual organization and discussion applied to the “journalistic column” genre”. In this manner, it exposes the context of the partnership developed between PIBID and extension. The workshop developed was a partnership between “pibidiano” and “extensionist”, both enrolled on the LET 438 (Discursive Genres) subject and both students of the Language course of the Federal University of Viçosa, also being a reflection on the possibilities of ways of applying the university extension. For the development of the workshop,the theories on discursive genres were relied on, as on Bakthin (2010), on textual notions proposed by Abreu (1994), Costa Val (1994) and Garcia (2015). The workshop had the objective of improving textual skills tied to discussion and textual organization through reading and knowledge on the “journalistic column” genre. For reaching this objective, the “didatic sequences” methodology,as on Barbosa (2017). The application of the workshop happened in a school gifted with PIBID from the state network of Viçosa (MG). Through the results, it could be perceived how it is possible to promote a critical view of midiatic productions and how the “journalistic column” genre is a bridge to the teaching of discussion.